Snow quality in urban areas - Viklander, Maria (Luleå tekniska universitet, Arkitektur och vatten, 1997)
The studies reported on this thesis aim to provide information and increase knowledge about the quality of urban snow and the path of pollutants. The results develop a basis for decisions regarding the prevention of environmental damage. A number of projects have been carried out to provide more detailed knowledge about: snow quality in cities, sediments that had accumulated during the winter, and that were left at the surface when the snow had melted, and the paths of pollutants at urban snow deposit. For these purposes studies have been performed in laboratory, pilot and full scale. The snow quality was studied in the city of Luleå with regard to variation with time and area. The aim was to investigate urban snow in its actual environment, throughout an entire winter season. Snow samples were taken in a housing area and in the city centre, at sites with different traffic load. It was found that traffic or activities related to traffic was a major source of heavy metals and phosphorus in urban snow, both in the city centre and the housing area. Also the type of area and the design of the street were important for the snow quality. A clear relation between the pH and the quantity of suspended solids in the snow was found. Higher pH values were found in snow from sites with higher traffic loads, compared to sites with small quantities of particles which were the no-traffic sites. The dissolved fractions showed more complicated results. The concentration of the studied substances in the snow was affected by the precipitation at the site with no traffic. At the street where the snow was left beside the street, the concentration of substances increased with time, while the precipitation was of less importance. The mass loads of substances increased with time for both the streets, where the snow stayed in the vicinity of the street, and for the non-traffic site. For the site with traffic the snow handling operations evidently affected the mass loads. This was especially the case for particle-connected substances. As ...